2021
DOI: 10.1177/19476035211012465
|View full text |Cite
|
Sign up to set email alerts
|

Shockwave Treatment Enhanced Extracellular Matrix Production in Articular Chondrocytes Through Activation of the ROS/MAPK/Nrf2 Signaling Pathway

Abstract: Objective Shockwave application is a potential treatment for osteoarthritis (OA), but the underlying mechanism remains unknown. Oxidative stress and a counterbalancing antioxidant system might be the key to understanding this mechanism. We hypothesized that reactive oxygen species (ROS) and the transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2),which is an important regulator of cellular redox homeostasis, are plausible elements. Design Porcine chondrocytes were cultured in a 3-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…In a recent study, a sulforaphane-activated Nrf2 signaling pathway was found to reduce allodynia and hyperalgesia while augmenting morphine’s antinociception [ 110 ]. Furthermore, a recent study found that activating Nrf2 reduced nociceptive hypersensitivity by reducing mitochondrial dysfunction and neuro-inflammation in a dimethyl fumarate-induced peripheral nerve injury model [ 111 ]. These findings suggest that the Nrf2 signaling pathway may be a promising therapeutic approach for chronic pain associated with knee OA treatment [ 112 , 113 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, a sulforaphane-activated Nrf2 signaling pathway was found to reduce allodynia and hyperalgesia while augmenting morphine’s antinociception [ 110 ]. Furthermore, a recent study found that activating Nrf2 reduced nociceptive hypersensitivity by reducing mitochondrial dysfunction and neuro-inflammation in a dimethyl fumarate-induced peripheral nerve injury model [ 111 ]. These findings suggest that the Nrf2 signaling pathway may be a promising therapeutic approach for chronic pain associated with knee OA treatment [ 112 , 113 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“… Nrf2 inhibition reduces shockwave-enhanced ECM synthesis. 144 Sox9 Primary chondrocytes isolated from bovine calves Physiological tensile strain (7.5% elongation, 1 Hz, 30 min) is applied. Physiological tensile strain induces SOX9 transcription and expression.…”
Section: Transcription Factors In Mechanotransduction Pathways In Cho...mentioning
confidence: 99%
“… 43 In our recent report, we found that shockwave treatment enhanced ECM synthesis in ACs through activation of the ROS/MAPK/NRF2 signalling pathway. 44 Furthermore, another study showed that increased stiffness and appropriate ROS production facilitates the chondrogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) by activating the mechanistic target of rapamycin (mTOR) signalling pathway. 45 Therefore, ROS are not categorically harmful, and therapeutics must consider the essential role of ROS levels.…”
Section: Discussionmentioning
confidence: 99%